Treatment of Retinopathy of Prematurity by Intravitreal Injection of Bevacizumab - Hossain, Mohammad Ismail; Khan, Kamrul Hasan; Sultana, Jesmin; Hasan, Zulfikar; Hossain, Billal; Kadir, Syeed Mehbub Ul (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Retinopathy of prematurity is a vasoproliferative disease of the developing retina that is a significant cause of paediatric morbidity and blindness worldwide. Although management by early treatment ROP (ETROP) criteria has led the way to improving the outcomes of treatment-requiring posterior (zone 1) ROP, the failure rate continues to be significant for aggressive disease. Managing a premature infant with ROP is a significant challenge to ophthalmologists and associated physicians. However, increasingly younger and lower birth-weight infants can survive with advances in neonatal care. Objectives: To assess the effectiveness of intravitreal injection of Bevacizumab on regression of retinal neovascularization in stage III, Zone 1, 2 retinopathy of prematurity and aggressive posterior retinopathy of prematurity. Methods: Intravitreal Injection of Bevacizumab (0.625mg/0.025mL) was performed on 34 eyes of 17 newborns with stage III, Zone 1, 2 retinopathy of prematurity and aggressive posterior retinopathy of prematurity. The changes in retinal neovascularization were assessed by frequent fundoscopy. Results: Retinopathy of prematurity regressed in all the eyes treated. The retinal vascularization proceeded beyond the demarcation line. Four eyes of 2 patients needed repeat injections. One eye needed an additional laser. There was no injection-related complication observed. Conclusion: Intravitreal injection of Bevacizumab can be considered an effective modality in treating Retinopathy of Prematurity. It is recommended to perform more studies to assess its long-term effect on the body's vascular system. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 24-27